2006
DOI: 10.4049/jimmunol.176.7.4258
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin-Sensitive Modulation of Intestinal Epithelial MD-2 as Mechanism of Lipopolysaccharide Tolerance

Abstract: Intestinal epithelial cells (IEC) are constantly exposed to both high concentrations of the bacterial ligand LPS and the serine protease trypsin. MD-2, which contains multiple trypsin cleavage sites, is an essential accessory glycoprotein required for LPS recognition and signaling through TLR4. The aim of this study was to characterize the expression and subcellular distribution of intestinal epithelial MD-2 and to delineate potential functional interactions with trypsin and then alteration in inflammatory bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…Soluble MD-2 may act as an acute-phase reactant in sepsis (61). Expression of MD-2 protein is significantly increased in the inflamed intestinal mucosa of patients with active IBD colitis (62). Here the exaggerated inflammatory response seen in TLR2/MDR1A double deficiency resulted from broken tolerance to commensal LPS via MD-2, as deletion of MD-2 markedly abrogated colitis exacerbation.…”
Section: Discussionmentioning
confidence: 92%
“…Soluble MD-2 may act as an acute-phase reactant in sepsis (61). Expression of MD-2 protein is significantly increased in the inflamed intestinal mucosa of patients with active IBD colitis (62). Here the exaggerated inflammatory response seen in TLR2/MDR1A double deficiency resulted from broken tolerance to commensal LPS via MD-2, as deletion of MD-2 markedly abrogated colitis exacerbation.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, expression of MD-2 is thought to be another important factor that determines the LPS responsiveness because optimal LPS recognition by TLR4 requires MD-2 as a coreceptor. It has been reported that MD-2 expression in healthy, normal intestinal mucosa is minimal, while it is increased in active inflammatory bowel disease colitis (33,34). Moreover, inhibition of CpG methylation and histone deacetylation was shown to result in increased mRNA expression of MD-2 gene in IECs just recently (35).…”
Section: Discussionmentioning
confidence: 99%
“…For preparation of subcellular fractions, the ProteoExtract subcellular proteome extraction kit from Merck was used according to the manufacturer's instructions. Immunoprecipitation/immunoblotting and mouse 62-cyto/chemokine antibody array III (RayBiotech) were performed as described previously (18,33). All of the experiments were repeated at least twice; representative results are shown for each experiment.…”
Section: Volume 284 • Number 33 • August 14 2009mentioning
confidence: 99%
“…Confocal Laser Microscopy-After mounting with Vectashield mounting medium with propidium iodide or DAPI (Vector Laboratories), immunofluorescent sections were assessed using a laser-scanning confocal microscope (Plan-Neofluar 40ϫ/1.3 (oil) or Plan-Apochromat 63ϫ/1.4 (oil) differential interference contrast objectives; Zeiss Axiovert 100M-LSM 510), as described previously (18,33). Briefly, the multitrack option of the microscope and sequential scanning for each channel were used to eliminate any cross-talk.…”
Section: Animals-mdr1␣mentioning
confidence: 99%